Improved limit on the branching fraction of the rare decay $${K ^0_{\mathrm { \scriptscriptstyle S}}} → μ ^+μ ^-$$ - Aaij, R; Adeva, B; Adinolfi, M; Evans, T; Gandini, P; Gruberg Cazon, B; Hadavizadeh, T; Harnew, N; Hill, D; Jalocha, P; John, M; Jurik, N; et al. (Springer, 2017)
A search for the decay $K^0_{\scriptscriptstyle S}→μ^+μ^-$ is performed, based on a data sample of proton-proton collisions corresponding to an integrated luminosity of 3 fb$^{-1}$, collected by the LHCb experiment at centre-of-mass energies of 7 and 8 TeV. The observed yield is consistent with the background-only hypothesis, yielding a limit on the branching fraction of ${\cal B}(K^0_{\scriptscriptstyle S}→μ^+μ^-) < 0.8~(1.0) × 10^{-9}$ at $90%~(95%)$ confidence level. This result improves the previous upper limit on the branching fraction by an order of magnitude.